Co-infection and localization of secondary symbionts in two whitefly species - Kontsedalov Svetlana (BMC Microbiology, 2010)
Abstract Background Whiteflies are cosmopolitan phloem-feeding pests that cause serious damage to many crops worldwide due to direct feeding and vectoring of many plant viruses. The sweetpotato whitefly Bemisia tabaci (Gennadius) and the greenhouse whitefly Trialeurodes vaporariorum (Westwood) are two of the most widespread and damaging whitefly species. To complete their unbalanced diet, whiteflies harbor the obligatory bacterium Portiera aleyrodidarum. B. tabaci further harbors a diverse array of secondary symbionts, including Hamiltonella, Arsenophonus, Cardinium, Wolbachia, Rickettsia and Fritschea. T. vaporariorum is only known to harbor P. aleyrodidarum and Arsenophonus. We conducted a study to survey the distribution of whitefly species in Croatia, their infection status by secondary symbionts, and the spatial distribution of these symbionts in the developmental stages of the two whitefly species. Results T. vaporariorum was found to be the predominant whitefly species across Croatia, while only the Q biotype of B. tabaci was found across the coastal part of the country. Arsenophonus and Hamiltonella were detected in collected T. vaporariorum populations, however, not all populations harbored both symbionts, and both symbionts showed 100% infection rate in some of the populations. Only the Q biotype of B. tabaci was found in the populations tested and they harbored Hamiltonella, Rickettsia, Wolbachia and Cardinium, while Arsenophonus and Fritschea were not detected in any B. tabaci populations. None of the detected symbionts appeared in all populations tested, and multiple infections were detected in some of the populations. All endosymbionts tested were localized inside the bacteriocyte in both species, but only Rickettsia and Cardinium in B. tabaci showed additional localization outside the bacteriocyte. Conclusions Our study revealed unique co-infection patterns by secondary symbionts in B. tabaci and T. vaporariorum. Co-sharing of the bacteriocyte by the primary and different secondary symbionts is maintained through vertical transmission via the egg, and is unique to whiteflies. This system provides opportunities to study interactions among symbionts that co-inhabit the same cell in the same host: these can be cooperative or antagonistic, may affect the symbiotic contents over time, and may also affect the host by competing with the primary symbiont for space and resources.